NON-STATIONARY NETWORK FLOW - Y.M. ERUSALIMSKY; N.N. VODOLAZOV (Advanced Engineering Research)
Non-stationary network flow is considered. Definitions of non-stationary network flow, amount of flow in T time, average amount of flow are given. Limitation on the average amount of flow is found.